(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Haemoparasites are either intracellular or extracellular organisms that inhabit the blood stream of vertebrate hosts. This study was conducted in Zaria Nigeria inorder to investigate the prevalence of haemoparasites in polo horses and their effects on haematological parameters. Blood samples were collected from a total of 100 randomly selected horses from polo stables across Zaria. The blood samples were screened and examined using thin blood smear, buffy coat technique, and differential white blood cell count. From the results thirteen horses 100(13%) were found infected with haemoparasites. The prevalence of Theileria equi in local and exotic breeds was 5(9.4%) and4 (8.5%) while for microfilaria it was 3(5.3%) and1 (2.1%). There were no Babesia or Trypanosomes found in the samples 0%. Among sexes the prevalence of Theileria equi and microfilaria in males was 1(7.7%) while in females it was (9.3%) and 3(3.4%).A high prevalence of Theileria equi and microfilaria was seen among old horses 6(9.3%) and4 (3.4%) compared to young 3(7.7%) and1 (7.7%).There was no significant association between the presence of the infection and its effect on haematological values (p>0.05). In conclusion some haemoparasites were found in polo horses in Zaria. It is hereby recommended that routine vector control and prophylactic treatment should be carried out in stables